Does the Ease of Starting a New Business Affect Country’s Financial Vulnerability? Evidence from Eight European Economies - Leviastuti, Anggita (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
This paper investigates whether indicators on the ease of doing business explain variation of financial system vulnerability amongst eight biggest European economics between 1999 and 2014. Using mixed-effects estimation method for sectoral observations nested within countries, the results suggest that easy access to get credit is associated with increased financial vulnerability, as measured by decreased excess return in equity market. The significance of political stability, regulatory quality, and rule of law also marks the role of institutional environment towards vulnerability by facilitating the openness towards new business. Finally, a high degree of openness is not always good especially if they are combined with better institutional environment. This confirms the importance of the level of openness, as well as its channels, in determining the extent of vulnerability.